A New European Market in Insurance Distribution - Mª Rocío Quintáns Eiras (LeXonomica, 2017)
The present work provides an approach to the main changes brought to the insurance market by the introduction of the Directive (EU) 2016/1997 of the European Parliament and of the Council of 20 January 2016, which comprises the recast of Directive 2002/92 on insurance mediation. The new Directive implements relevant changes with the paramount aim of reaching a harmonization of the different national provisions concerning insurance and reinsurance distribution of the EU, both on the application scope and on the insurance consumer protection.